Meta-Analisis Pendekatan Pembelajaran Konstruktivisme dalam Meningkatkan Hasil Belajar Siswa Pada Pembelajaran IPS Sekolah Dasar - Dewi Fitria; Mila Lestari; Siti Aisyah; Renita Renita; Dasmini Dasmini; Safrudin Safrudin (Universitas Nusantara PGRI Kediri, 2021)
This study aims to re-analyze the constructivism learning approach in improving student learning outcomes in elementary school social studies learning. In this study using the meta-analysis method. Research data collection is carried out by researchers by browsing articles contained in online journals, thesis or dissertation results in the repository, using Google Scholar or Cedekia. The source of data (articles) taken is data (articles) from 2016-2021. From the search results obtained 10 relevant articles that have been published in online journals. The results of the analysis show that constructivism learning is able to improve student learning outcomes from the lowest 9.80% to the highest 75.00% with a significant increase of 24.05%.